Contribution of disturbed iron metabolism to the pathogenesis of Parkinson''s disease. (July 2008) - Berg, Daniela; Riederer, Peter; Gerlach, Manfred
Extensive research has revealed a complex pathophysiology in Parkinson''s disease, with different factors contributing to the progressive neurodegeneration. Within this complex pathophysiology, a central role of iron and iron-induced oxidative stress has been discussed for many years, as elevated tissue iron levels, especially within the substantia nigra, have been detected by different techniques in a number of postmortem studies. These findings could be verified intra vitam by advancing MRI techniques, and more recently transcranial ultrasound. Different causes, such as disruption of the BBB, local changes in the normal iron-regulatory system, release of iron from intracellular storages or intraneuronal transportation from iron-rich areas, as well as genetic variations leading to changes in brain iron metabolism, are being discussed to be responsible for the increased tissue iron levels. Although it is still not clear whether increased iron levels constitute a primary or secondary phenomenon in the etiology of Parkinson''s disease, its interaction with many pathophysiologcial cascades and contribution to all forms of Parkinson''s disease, idiopathic as well as monogenetic, stresses the importance of further elucidating the mechanism of brain iron homeostasis and its possible alterations to finally develop pharmacological interventions that may disrupt the chain of pathological events leading to neurodegeneration.